DEVELOPMENT OF THE MECHANISM OF THE INVESTMENT ANALYSIS IN THE CONDITIONS OF UNCERTAINTY - N. A. Kharitonova; A. A. Bukreeva (Стратегические решения и риск-менеджмент)
The article runs about the necessity of improvement method of account efficiency of the investment project in condition unstable economic development. In article offered a method of reducing investment risk in the account of the investment project of real option method in condition indeterminacy. For this purpose developed the formula for determining the discount rate of each scenario of events. In addition, authors develop the concept of construction of stages for the purpose of definition of scenarios of the investment project and their probability with a view of overcoming of the basic problems of use of multiscenary model for estimation of cost of real options. For the purpose of decrease in risks of the operating enterprise both classification of real options is developed for a conclusion of the enterprise from crisis, and as a preventive measure, with instructions of sources of financial resources